2011
DOI: 10.1111/j.1728-4457.2011.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridges to Nowhere: Hosts, Migrants, and the Chimera of Social Capital in Three African Cities

Abstract: Interest in migrant social networks and social capital has grown substantially over the past several decades. The relationship between “host” and “migrant” communities remains central to these scholarly debates. Recently urbanized cities in Africa, which include large numbers of “native-born” or internal migrants, challenge basic presumptions about host/migrant distinctions informing many of these discussions. Using comparable survey data from Johannesburg, Maputo, and Nairobi, we examine 1) the nature of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…That is why some migrants argued that the same could still happen to them or other people in Zimbabwean cities such as Harare or Bulawayo. These findings concur with Madhavan and Landau's (2011) study of three African cities, which revealed that there is a general disenfranchisement and lack of collective solidarity even among kin.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…That is why some migrants argued that the same could still happen to them or other people in Zimbabwean cities such as Harare or Bulawayo. These findings concur with Madhavan and Landau's (2011) study of three African cities, which revealed that there is a general disenfranchisement and lack of collective solidarity even among kin.…”
Section: Resultssupporting
confidence: 90%
“…Literature elsewhere has already shown how family members and other migrant networks have become hostile to newcomers and in some cases, are beginning to redirect them elsewhere (Collyer 2005;Korinek, Entwisle & Jampaklay 2005;Menjivar 1995;1997) and how migrants lack collective solidarity (Madhavan and Landau 2011). Starting recently, an attempt is being made to understand preference for friends rather than family among Zimbabweans in Botswana by Mutsindikwa and Gelderblom (2014) who mainly explain the deterioration of family relations as consequences of the economic collapse and excessive downward mobility in Zimbabwe that increased competition for resources and reduced solidarity among kin.…”
Section: Introductionmentioning
confidence: 99%
“…As there is a recent history of the native‐ and foreign‐born competing in marginalized urban spaces in South Africa ( see Misago, Landau, and Monson, ; Landau, ) as well as competition among the native‐born, it would seem that individuals in these groups would be unlikely to develop strong social ties to one another; however, recent evidence in South Africa suggests that trust – as an indicator of social capital – varies between foreign and native‐born groups (Madhavan and Landau, ), even if the mechanisms behind this variation are still unknown. As the literature on social capital tends to suggest that the development of cohesive communities across various groups is advantageous to individuals and the larger population, and that individual ties across social groups allows individuals to access scarce resources that improve people's livelihoods, even a minimal amount of civic engagement and trust between groups in Johannesburg may have dramatically reduced the death count, destruction of property, and overall xenophobic tensions in 2008 (Steenkamp, ).…”
Section: Johannesburg South Africamentioning
confidence: 99%
“…Madhavan and Landau, 2011). This is, to a certain extent, reflected in the different groups' level of organisation.…”
Section: Farming Systems Subsistence and Marketingmentioning
confidence: 99%